EFEKTIVITAS PROGRAM ACARA 86 NET TERHADAP PENINGKATAN KESADARAN TERTIB BERLALU LINTAS (Studi Kasus Masyarakat Kota Bogor) - Rizqy Febriawan; Feri Ferdinan Alamsyah; Diana Amaliasari (Jurnal Penelitian Sosial Ilmu Komunikasi, 2021)
This research aims to identify the effectiveness of program 86 NET TV on increasing driving awareness of Bogor City community. The data analysis technique uses a quantitative explanatory survey method by taking data through a questionnaire, and document.The results of the research based on the effectiveness of the program 86 NET (X) significantly affects the community's awareness of driving (Y). The results of the calculation of the coefficient of determination test show that the effectiveness of the program affects driving awareness by 49.5 percent, meaning that it is not only the program effectiveness factor that affects public awareness of driving